The Confrontation between Sympathizers and Opponents of Franco in Editorial Católica, Publisher of the "Ya" newspaper (1945-1958) (Communication & Society, 2001)
This work focuses on the confrontation between sympathizers and opponents of General Franco, in La Editorial Católica, a confessional publishing house of both books and papers. The leading opponent, Francisco de Luis, was a main manager in the company, who, with a group of friends, pretended –if possible- to avoid any matter about Franco’s regime in their publications. The sympathizers, leaded by the Bishop of Málaga, wanted to help Franco in his secundary education reforming plan, and in other cultural values which higly displeased the Church in Spain. The confrontstion ended with the expellation of Francisco de Luis from the publishing house, in 1958.